2007
DOI: 10.1111/j.1365-2729.2007.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering simulations in science education at a distance: features of effective use

Abstract: This paper proposes a reconsideration of use of computer simulations in science education. We discuss three studies of the use of science simulations for undergraduate distance learning students. The first one, The Driven Pendulum simulation is a computer-based experiment on the behaviour of a pendulum. The second simulation, Evolve is concerned with natural selection in a hypothetical species of a flowering plant. The third simulation, The Double Slit Experiment deals with electron diffraction and students ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 20 publications
2
72
0
7
Order By: Relevance
“…In a second condition, the variables were integrated but unlinked, and, in a third, they were both unlinked and unintegrated. The authors found that students who learned the most were best able to transfer their new knowledge to new problems, and that these same students reported the least difficulty with the version that was both linked and integrated-a finding that expands upon the design principle of ''multiple representations'' (Blake and Scanlon 2007). However, intergroup differences emerged only when more challenging problems were presented to the students.…”
Section: Introductionmentioning
confidence: 88%
“…In a second condition, the variables were integrated but unlinked, and, in a third, they were both unlinked and unintegrated. The authors found that students who learned the most were best able to transfer their new knowledge to new problems, and that these same students reported the least difficulty with the version that was both linked and integrated-a finding that expands upon the design principle of ''multiple representations'' (Blake and Scanlon 2007). However, intergroup differences emerged only when more challenging problems were presented to the students.…”
Section: Introductionmentioning
confidence: 88%
“…Computer assistance has the potential to reduce the complexity of phenomena, to focus on a smaller set of items and variables, and to offer a 'model progression' over several levels . Further measures support successful learning with simulations, among them the use of multiple representations, 'tailorability' of tools (Blake & Scanlon, 2007), prompting for reflective activities (Pilkington & Parker-Jones, 1996;White & Frederiksen, 1998), and interpretative cues (Reid, Zhang, & Chen, 2003) projections. Additionally, the project gives students a short list of appropriate web links where they can deepen the knowledge gained so far.…”
Section: Tools Supporting Investigationsmentioning
confidence: 99%
“…Among computer-based learning programs, computer simulations are considered to be the most technically sophisticated option for offering various benefits for the teaching and learning of science (Blake and Scanlon 2007). A computer simulation is an interactive program that contains a model of a natural or artificial system or process (Blake and Scanlon 2007;.…”
mentioning
confidence: 99%
“…A computer simulation is an interactive program that contains a model of a natural or artificial system or process (Blake and Scanlon 2007;. It gives learners opportunities to experiment harmlessly and to simulate processes in an e-learning environment (Urhahne et al 2000).…”
mentioning
confidence: 99%